Contrasting patterns of environmental fluctuation contribute to divergent life histories among amphibian populations. Issue 4 (8th April 2016) - Cayuela, Hugo; Arsovski, Dragan; Thirion, Jean‐Maric; Bonnaire, Eric; Pichenot, Julian; Boitaud, Sylvain; Brison, Anne‐Lise; Miaud, Claude; Joly, Pierre; Besnard, Aurelien
Abstract: Because it modulates the fitness returns of possible options of energy expenditure at each ontogenetic stage, environmental stochasticity is usually considered a selective force in driving or constraining possible life histories. Divergent regimes of environmental fluctuation experienced by populations are expected to generate differences in the resource allocation schedule between survival and reproductive effort and outputs. To our knowledge, no study has previously examined how different regimes of stochastic variation in environmental conditions could result in changes in both the temporal variation and mean of demographic parameters, which could then lead to intraspecific variation along the slow–fast continuum of life history tactics. To investigate these issues, we used capture–recapture data collected on five populations of a long‐lived amphibian ( Bombina variegata ) experiencing two distinct levels of stochastic environmental variation: (1) constant availability of breeding sites in space and time (predictable environment), and (2) variable spatio‐temporal availability of breeding sites (unpredictable environment). We found that female breeding propensity varied more from year to year in unpredictable than in predictable environments. Although females in unpredictable environments produced on average more viable offspring per year, offspring production was more variable between years. Survival at each ontogenetic stage was slightly lower and varied significantly more from year to year in unpredictable environments. Taken together, these results confirm that increased environmental stochasticity can modify the resource allocation schedule between survival and reproductive effort and outputs and may lead to intraspecific variation along the slow–fast continuum of life history tactics.